Reducing the Power of the Alcohol Industry in Trade and Investment Agreement Negotiations Through Improved Global Governance of Alcohol; Comment on "What Generates Attention to Health in Trade Policy-Making? Lessons From Success in Tobacco Control and Access to Medicines: A Qualitative Study of Australia and the (Comprehensive and Progressive) Trans-Pacific Partnership" - Paula O'Brien (Kerman University of Medical Sciences, 2022)
The power of the alcohol industry pervades the global governance of alcohol. The influence of the industry is seen in trade and investment treaty negotiations, operating through direct and indirect means. Curbing the influence of the industry is vital to improving the treatment of health issues generally and in trade and investment policy particularly. The World Health Organization (WHO) has an opportunity to start to rein in the power of the industry with its current work on drafting an 'action plan' for 2022-2030 to implement the Global Strategy to Reduce the Harmful Use of Alcohol. The WHO working paper, however, proposes inadequate controls on alcohol industry influence. The WHO proposes 'dialogue' with the industry and allows the industry to take a role with government in public health labelling of alcohol. The public's health will suffer if the WHO does not take a firmer stand against the industry in the 'action plan.'